Die Wuchshöhenregel der ökologischen Pflanzengeographie - Schwarz, Reiner (ERDKUNDE, 1999)
A generally positive correlation between maximum leaf height of a plant formation and the general favouring of vegetation growth is put forward. This apparent and sometimes unwittingly documented relationship has not been formulated until recently. It is not clear why the phenomenon remained unnoticed for such a long time. The theory underpinning it is by no means trivial. It is based on the competition for light and the related growth in height stimulated by canopy leaf density, which for its part is reduced by the genetically fixed necessity of investments to cope with stress and competition for resources supplied through the soil. An attempt is made to represent the theory in a uniform way by systems analysis. Its consistency with observation is discussed. Relevant observations can only be made where plant competition is able to work, as is the case with extensive cattle grazing or natural forestry. The explanation fails if growth in height offers advantages not favouring competition for light but for fire protection.